Analysis of electronic properties frommagnetotransport measurements on Ba(Fe1-xNix)2As2 thin films - Shipulin, Ilya; Richter, Stefan; Thomas, Aleena Anna; Nielsch, Kornelius; Huehne, Ruben; Martovitsky, Victor (Materials, 2020)
We performed a detailed structural, magnetotransport, and superconducting analysis of thin epitaxial Ba(Fe1-xNix)2As2 films with Ni doping of x = 0.05 and 0.08, as prepared by pulsed laser deposition. X-ray diffraction studies demonstrate the high crystalline perfection of the films, which have a similar quality to single crystals. Furthermore, magnetotransport measurements of the films were performed in magnetic fields up to 9 T. The results we used to estimate the density of electronic states at the Fermi level, the coefficient of electronic heat capacity, and other electronic parameters for this compound, in their dependence on the dopant concentration within the framework of the Ginzburg-Landau-Abrikosov-Gorkov theory. The comparison of the determined parameters with measurement data on comparable Ba(Fe1-xNix)2As2 single crystals shows good agreement, which confirms the high quality of the obtained films.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Electronic properties; Iron-based superconductors; Pulsed laser deposition; Thin films